Empowerment Strategy for BUMDes-Assisted MSMEs through Management and Technology Innovation in Tanara Village - Dewi, Irma Nurmala; Romli, Ombi; Khaerudin, Dedy (International Journal of Research in Community Services, 2025)
BUMDes Tanara, located in Tanara District, Serang Regency, Banten Province, has good potential for empowering MSMEs fostered by Tanara BUMDes. Tanara BUMDes has developed partnerships with home industries that are capable of competing with other home industry products in the vicinity of Tanara Village and with various MSME products. Home industry actors frequently encounter challenges such as the absence of technology in their production processes, business mentoring and socialization activities conducted by BUMDes or other entities, and marketing that is still performed manually and does not take advantage of e-commerce assistance or technology. This community service aims to provide knowledge and skills to BUMDes fostered partners in increasing the use of technology and business mentoring, especially in marketing, which the PKM team will carry out through socialization and salesmanship training. Therefore, the community service carried out by the PKM team of Bina Bangsa University, funded by DPPM Kemendiktisaintek, for the Fiscal Year 2025, can provide solutions to Tanara BUMDes fostered partners. The method used was gradual outreach and counseling for BUMDes Tanara's fostered partners. The results of the outreach and counseling activities conducted by the Community Partnership Empowerment (PKM) team demonstrated that mentoring and outreach regarding science and high technology needs for the home industry players, fostered by BUMDes Tanara.